To dance or not to dance for the country: the paradox of (in)decent dances at the dawn of the Republic (Peru, 1825-1860) (Revista Argentina de Musicología, 2023)
Carlos Vega and Isabel Aretz carefully studied the Peruvian origin of some dances from the time of Independence and that survived in Argentine territory in the ﬁrst half of the 20th century such as El Cuándo, El Chocolate, El Mismis and La Mariquita. However, very little is known about examples and uses of these dances in Peruvian territory. The boom that these dances experienced among the elites of the Peruvian viceroyalty and that later motivated their fast displacement towards neighboring countries speaks of preferences for certain repertoires with certain textual, sound, and choreographic characteristics that positioned them as sound representations of Americanity and therefore carriers of meaning around the construction of alternative identities to the Hispanic one. However, within a period of thirty years, such dances gave way to others of European or national origin and lost preponderance in Lima’s salons as they were considered incompatible with the notions of decency and modernity to which the ruling classes of the young republic they wanted to join. Through the study of musical examples from the Kestner collection of the Hannover Library and primary sources of the time, this work seeks to establish links between these dances and the discourses and imaginaries associated with their permanence and oblivion in Peruvian society of the ﬁrst half of the tenth century.
Keywords: Peruvian music of the 19th century; Sesquialtera dances; Kestner Collection; Peruvian dances; South American dances